ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO PROFITABILITAS PADA PTPN XIV (PERSERO) MAKASSAR - Rusdi, H Muh; Arianita, Evi (Perpustakaan dan Penerbitan Unismuh Makassar, 2012)
The purpose of this study is to determine the development of Financial Performance based on Profitability Ratio in PTPN XIV (Persero) Makassar 2011-2013. The research was conducted by Profitability Ratio Method. This method uses four indicators, namely: Gross Prifit Margin, Net Profit Margin, Return On Investment, and Return On Equity that measures financial performance based on Profitability Ratio. The data obtained in the form of documents in the form of Financial Statements, and data obtained in the form of file in the form of general overview of the company, namely data collection through direct interviews in the Accounting, Finance, and HR, related to the problems studied at PT. Perkebunan Nusantara XIV (Persero) Makassar. The results of this study concluded that In Gross Prifit Margin, Net Profit Margin, and Return On Equity which measures financial performance based on Profitability Ratio, financial performance in 2011-2013 at PTPN XIV (Persero) Makassar increased from year to year except Return On Investment experienced the decrease in 2011-2012 amounted to -63.53% and an increase in 2012-2013 amounted to 312.41% so the Return On Investment company improved then the hypothesis rejected.